Validity of teaching modules based on local wisdom of macroscopic fungi and PjBL-oriented to improve scientific attitudes and science literacy - Asti Lovina Sary; I. Isnawati; Mahanani Tri Asri (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
One of the government's efforts to improve the quality of education in Indonesia is through curriculum changes. The independent curriculum prioritizes learning related to local wisdom. However, many teachers still need to implement learning in schools linked to the local wisdom of the area around students. This research aims to produce and validate a teaching module based on the local wisdom of macroscopic fungi at TAHURA Mojokerto with a Project-Based Learning (PjBL) orientation to improve scientific attitudes and science literacy. This development research was carried out using a 4D Thiagarajan Model. The analysis was carried out using a quantitative descriptive analysis technique. The data comes from the validation process by two expert lecturers. The results of the validity test of the learning plan obtained an average score of 3.56; the results of the validity test of learning media in the form of a macroscopic fungi herbarium, teaching materials "Kingdom Fungi", the Edible Mushroom booklet obtained an average score of 3.72; student worksheet validity test results received an average score of 3.52. The results of the recapitulation of validity data show a total score of 3.6 with a very valid category. Based on the results obtained, it was concluded that teaching modules based on macroscopic fungi local wisdom at TAHURA Mojokerto are PjBL-oriented to improve scientific attitudes and science literacy worthy of being applied in Biology learning at school.